Sample size definition for food composition analysis - PortFIR development based on EuroFIR experience - Dias, M. Graça (2014)
Background. To define the number of samples or sample size needed to provide a representative nutrient mean value requires information on natural variability and on the contribution of a particular food for nutrient intake. Obtaining nutrient analytical values to define a sampling plan involves many resources, and there is no nutrient/food country specific literature to support this task, therefore sharing and managing information among all food chain intervenient is crucial. Objectives. To gather information and knowledge among food data producers and users to create a Food Sampling Guide to support chemical analysis for Food Composition Databases as well as for nutritional labelling and control. Material and Methods. A Sampling Working Group (GTA) was established within EuroFIR inspired PortFIR’s Food Composition Network to elaborate a Sampling Guide for chemical analysis of food Results. GTA decided the guide should include indications about weighing variability and food consumption/nutrient intake in the definition of the sample size for nutrient quantification and chose to start focusing on three food groups, milk and dairy products, meat and meat products, and olive oil, oils and fats, to obtain food consumption data and gather nutrient analytical information to document natural variability. Based on Portuguese food balance sheet relevant food contributors for protein, fat, calcium, iron, SFA, MUFA and PUFA were established. Variability of those nutrients in relevant foods is under study and also criteria to define the accuracy required to produce mean nutrient values. Conclusions. The cooperation between data producers is contributing to optimize the usage of National resources to produce a guide with indications about weighing variability and food consumption/nutrient intake in the definition of the sample size.